1964
DOI: 10.1002/anie.196407691
|View full text |Cite
|
Sign up to set email alerts
|

Recoil Reactions of Tritium with Organic Compounds

Abstract: After "coolinx", the hot tritium atoms formed above thermal energies by nuclear reactions abstract or replace hydrogen atoms, and replace subytituents X (e.g. alkyl, NH2, N02, OH, COOH, F, Cl, Br, or I ) in organic compounds. Isotope eJfects have been obserwd for protonated vs. deuterated compounds in several hot reactions. Models and mechanisms are discussed for the abstraction and replacement, for specific reactions on certain carbon atoms, and for the isotope ejects. These are based on steric, bond-energy, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1966
1966
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…2-6 Earlier investigations of the relative yields of halogen reactions such as (1) have served as the basis for theories concerning the nature of these energetic processes. [11][12][13][14] Earlier experiments have demonstrated that the ob- Our present experiments have sought additional information about reaction 1 with X = F, C1, Br, and I and lead to the conclusion that the relative yields of these substitution reactions increase markedly with decreasing C-X bond strength.…”
mentioning
confidence: 78%
“…2-6 Earlier investigations of the relative yields of halogen reactions such as (1) have served as the basis for theories concerning the nature of these energetic processes. [11][12][13][14] Earlier experiments have demonstrated that the ob- Our present experiments have sought additional information about reaction 1 with X = F, C1, Br, and I and lead to the conclusion that the relative yields of these substitution reactions increase markedly with decreasing C-X bond strength.…”
mentioning
confidence: 78%
“…A great deal of experimental data has been collected in recent years and several excellent reviews have summarised the development of this ever-growing field of study [1,2,3], Particular attention has been paid to the study of recoil tritium chemistry, largely due to the efforts of F. S.…”
Section: Introductionmentioning
confidence: 99%
“…ROWLAND [3], D. S. URCH [2] and the late RICHARD WOLFGANG [1,4]. At one time it seemed that a general agreement on the nature of recoil tritium reactions with simple molecules was within easy reach [5], However, in recent years a number of experimental results have been reported which have led to considerable disagreement and confusion.…”
Section: Introductionmentioning
confidence: 99%
“…In 1934, Szilard and Chalmers were the first to describe a direct chemical consequence of a nuclear reaction (8). They showed that neutron irradiation of liquid ethyl iodide yields water extractable, radioactive iodine.…”
mentioning
confidence: 99%
“…The chemical consequences of such reactions have been studied in great detail in a multitude of different systems and these studies have lead to the modern kinetic concept of "hot atom reactions" (6)(7)(8).…”
mentioning
confidence: 99%